Detection of Salmonella in Food Samples by Dot-ELISA using Polyclonal Antibody - Krisada Tuchinda; Boontharika Naknam; Patcharee Sunthornandh; Chaiwat Kittikul; Ong-ard Lawhavinit (Agriculture and Natural Resources, 2011)
The immunological method of dot-ELISA(enzyme linked immunosorbent assay) was performed using a polyclonal antibody produced in rabbits immunized with Salmonella ser. Anatum and Salmonella ser. Enteritidis. The purification of immunoglobulin G (IgG) was carried out by affinity chromatography and the purity was characterized by SDS-PAGE. The purified IgG was used to detect Salmonella by the dot-ELISA method. It was found that all Salmonella serovars representative of each group were positive. However, there was cross reaction with other enteric Gram-negative bacteria. Therefore, Rappaport Vassiliadis Soya (RVS) selective enrichment broth was used to select and increase the number of Salmonella (but inhibit the other enteric Gram-negative bacteria) which then were examined by the dot-ELISA method. It was found that this method was able eliminate the cross reaction as well. Detection of Salmonella from food samples using RVS broth followed by the dot-ELISA method, compared with a modified standard method (ISO 6579:2002) was performed. Forty-eight out of 175 food samples (27.43%) were positive for salmonellae detection which was the same result as by the standard method. Detection using RVS broth followed by the dot-ELISA method took only 24 h, which was shorter than the standard method. Moreover, determination by the dot-ELISA method was easy and used lower amounts of reagents, as well as being cheaper and highly sensitive.